Conspectus of the genus Juniperus L. growing in Kazakhstan - M. M. Yermagambetova; S. I. Abugalieva; Ye. K. Turuspekov; Sh. S. Almerekova (Труды по прикладной ботанике, генетике и селекции, 2022)
Background. The genus Juniperus L. is the most numerous in the family Cupressaceae Bartl. and includes about 75 species. There are from 7 to 10 species of this genus in Kazakhstan. All types of juniper are widely used in folk medicine and play an important ecological role. The purpose of our work was to study the current status, systematics and distribution of juniper species. This will help to clarify and expand the information on the current location of Juniperus species in Kazakhstan and will be used in the future to study intra- and interspecific genetic diversity of the genus.Materials and methods. To study the distribution and make a conspectus of the Juniperus spp. growing in Kazakhstan, floristic reports, materials of plant explorations and the herbarium collections for the period from 1890 to 2021 obtained from the herbarium of the Institute of Botany and Phytointroduction (AA), herbarium materials of the Institute of Plant Biology and Biotechnology as well as the digital herbarium of the Lomonosov Moscow State University – Depository of Living Systems “Noah’s Ark” (MW) were analyzed.Results. As a result of the study, 630 herbarium sheets were processed and 70 locations of 7 juniper species growing in Kazakhstan belonging to 2 sections – Juniperus (=Oxycedrus Endl.) and Sabina Endl. – were identified. A conspectus of 7 juniper species identified during the analysis of the three above-mentioned herbarium collections was made. The main division of species is observed in the context of administrative and floristic regions of Kazakhstan. The greatest species concentration occurs in Southern, South-Eastern and Eastern Kazakhstan. The results of the study contribute to the inventory and search for previously forgotten places of growth for the genus Juniperus. Besides, the continuation of comprehensive botanical and molecular genetic studies on junipers will help to examine and preserve the genetic diversity of the species and conserve forest bioresources.